2019
DOI: 10.2147/idr.s204025
|View full text |Cite
|
Sign up to set email alerts
|

<p>Outcomes of therapeutic keratoplasty for severe infectious keratitis in Chongqing, a 16-year experience</p>

Abstract: Purpose This study aimed to evaluate the outcomes of therapeutic keratoplasty for severe infectious keratitis in Chongqing (Southwest China). Patients and methods The records of 561 eyes that underwent therapeutic keratoplasty for refractory microbial keratitis from 2001 to 2016 were analyzed in this retrospective study. Data included demographic information, microbiological investigations, associated factors, graft size, preoperative status, postoperative complications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…This is reflected within a study conducted in India whereby 75% of patients were from rural communities, with a high rate (28%) of PKIK being observed ( 45 ). Additionally, a China study reported farmers to be a significant independent risk factor of PKIK due to higher risk of trauma, particularly from plants resulting in fungal keratitis ( 57 ). These populations also have a higher risk for non-compliance of post-operative medication administration and hygiene ( 58 ).…”
Section: Epidemiologymentioning
confidence: 99%
“…This is reflected within a study conducted in India whereby 75% of patients were from rural communities, with a high rate (28%) of PKIK being observed ( 45 ). Additionally, a China study reported farmers to be a significant independent risk factor of PKIK due to higher risk of trauma, particularly from plants resulting in fungal keratitis ( 57 ). These populations also have a higher risk for non-compliance of post-operative medication administration and hygiene ( 58 ).…”
Section: Epidemiologymentioning
confidence: 99%
“… 22 24 In severe cases of medically uncontrollable infectious keratitis, surgical interventions and corneal keratoplasty are the last therapeutic alternatives; however, these are often associated with poor visual outcomes and increased risks of graft rejection/failure. 25 27 Moreover, major shortage of corneal graft, with only one in 70 patients worldwide having access to donor tissue is an additional challenge. 28 …”
Section: Introductionmentioning
confidence: 99%
“…Using the discrete model in CFD, namely DPM model, which in practical application is suitable for cases where the volume fraction of discrete phase in fluid domain is less than 10 ~12% [7][8] . In this paper, the Euler-Lagrange method is used to calculate the flow states associated with continuous phase and discrete phase, and the one-way coupling [9][10] method is used. See Table 1 for particle parameter settings.…”
Section: Simulation Parameter Settingmentioning
confidence: 99%